Stromal cell-derived factor-1 may play pivotal role in distraction-stimulated neovascularization of diabetic foot ulcer. (April 2021) - Fang, Jiezhuang; Xu, Jiankun; Zhang, Yuantao; Chen, Hongjiang; Ma, Zebin; Huang, Zhonglian; Hu, Jun
Abstract: Diabetic foot ulcer (DFU) has become a major medical, social and economic concern worldwide. It is highly desirable to develop promising new solutions to effectively and appropriately treat DFU. In recent years, investigators have used an innovative technology called proximal tibial cortex transverse distraction (PTCTD) to treat DFU and have achieved satisfactory results in terms of improved wound healing and circumvention of amputation as a consequence of enhanced neovascularization and perfusion of the ulcerated feet after the operation, but the underlying mechanism has not been explored. Previous studies have suggested that in addition to stimulating osteogenesis, bone distraction also facilitates neovascularization, which may be associated with the chemokine stromal cell-derived factor-1 (SDF-1). As an important member of the chemokine family, SDF-1 is primarily responsible for the homing and migration of endothelial progenitor cells (EPCs) or bone marrow-derived mesenchymal stem cells (BMSCs), and plays a central role in the process of neovascularization. In vivo or in vitro experiments show that bone distraction can induce the expression of SDF-1 and increase its plasma concentration. Moreover, some researchers have found that an insufficient level of SDF-1 in the circulation and wounds of patients with DFU can lead to impaired neovascularization. Therefore, we believe that SDF-1 plays an important role in promoting neovascularization of DFU as a result of bone distraction. We summarize the currently relevant literature to put forward an undisclosed but meaningful mechanism of bone distraction in the treatment of DFU.